Perkembangan Karya Misi Gereja Katolik di Kedang Ipil (Tinjauan Panca Tugas Gereja) - Andri Yanus; Wilfridus Samdirgawijaya; Silpanus Silpanus (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2019)
The purpose of this research is to know and describe Inputs, Processes, and Outputs of the development of mission work. And analyze the relationship between the condition of the present people with the historical process. This research uses descriptive qualitative method with interview, documentation, and observation methods. The results of the study stated that: (1) St. Catholics Paulus Kedang Ipil initially adopted the traditional belief system, namely animism. (2) Their early periods of adopting Catholicism experienced many obstacles. Starting from internal to external problems that occur within the Church to the community. (3) Finally entering the